The dual role of palladium in enhancing the photocatalytic activity of CdS dispersed on NaY-zeolite. Issue 10 (12th February 2015) - Sasikala, R.; Gaikwad, A. P.; Sudarsan, V.; Rao, R.; Jagannath,; Viswanadh, B.; Bharadwaj, S. R.
Abstract : A stable photocatalyst, CdS dispersed on zeolite with Pd as both dopant and co-catalyst, exhibits enhanced photocatalytic activity. Abstract : A stable photocatalyst, CdS dispersed on zeolite with Pd as both the dopant and the co-catalyst, has been developed. Enhancement of photocatalytic activity for hydrogen generation is observed for CdS when doped with palladium and dispersed on NaY-zeolite (CdPdS-Z). A further increase in the photocatalytic activity of CdPdS-Z is observed when palladium is added as a co-catalyst (Pd-CdPdS-Z). Cd0.95 Pd0.05 S-Z is synthesized via a facile soft chemical route and the Pd co-catalyst is loaded onto the composite using a wet impregnation method. This composite catalyst exists as two phases consisting of CdPdS and zeolite and CdPdS exists as a highly dispersed phase on zeolite as revealed by TEM studies. The Pd doped CdS–zeolite composite exhibits increased visible light absorption indicating the alteration of the band structure of CdS as a result of doping. Time resolved fluorescence studies reveal that the lifetime of the charge carriers is higher in the composites than in pure CdS. A detailed characterization using XRD, Raman and X-ray photoelectron spectroscopy indicates that Pd has substituted for Cd in the CdS lattice and Pd exists in the Pd 2+ oxidation state. Solid state MAS NMR studies indicate that an interaction exists between CdS (or CdPdS) and zeolite at the interface and Cd selectively interacts with Al of the zeolite framework. The photocatalytic activity of the Pd-CdPdS-Z catalyst remains unchanged with repeated cycles. Characterization of the used catalyst indicates that it is stable under the present experimental conditions. The enhanced photocatalytic activity of Pd-CdPdS-Z is attributed to the enhanced visible light absorption arising due to Pd doping and increased lifetime of the photogenerated charge carriers assisted by zeolite and the Pd co-catalyst. This study highlights the multiple roles played by palladium in enhancing the photocatalytic activity of the CdS–zeolite composite.